How Wartime Bonds Affect Ex-Combatant Political Attitudes: A Natural Experiment with the FARC - Sharif, Sally (Terrorism and political violence, 2023)
What determines political attitudes of ex-combatant after conflict, specifically the inclination towards rearmament? And to what extent do these attitudes depend on ex-combatants’ individual profiles? I argue that ex-combatant political attitudes are determined by whether wartime bonds are maintained after conflict. The argument indirectly implies that the impact of individual characteristics, such as gender, age, education, time in conflict, and family relations, fade in the face of group-level factors determined both during and after conflict. The argument highlights the challenge of post-conflict peacebuilding, where keeping intact the organizational structure of rebel groups might lead to peace but discourage reintegration into the country’s political (non-rebel) institutions. The Colombian Disarmament, Demobilization, and Reintegration (DDR) program’s design with a long demobilization process in camps lends itself to a natural experiment to distinguish community effects from individual-level influencers of ex-combatant political attitudes. Relying on data I have collected through 121 semi-structured, in-depth interviews with FARC ex-combatants residing in five ETCR, I find ex-combatants that have maintained their primary group cohesion in the post-conflict era have stronger secondary group cohesion, more favorable attitudes towards DDR, and less enthusiasm towards rearming. However, they have less trust in the government.